Etiology of Mental Retardness - Umarova Saboxon Minavvarovna; Valiyeva Shohsanam Baxtiyorjon qizi (International Journal on Orange Technologies, 2021)
The causes of mental retardation can be various: internal and external factors, hereditary disorders, infectious diseases during pregnancy, birth injuries, metabolic disorders, disorders of genetic metabolism in cells, injuries and others.